1986
DOI: 10.1152/jappl.1986.61.2.785
|View full text |Cite
|
Sign up to set email alerts
|

Rat lung microsomal lipid peroxidation: effects of vitamin E and reduced glutathione

Abstract: Lung microsomal membranes that contain the redox active components associated with the mixed-function oxidase system can be peroxidized in vitro. To investigate the characteristics of rat lung microsomal lipid peroxidation, we performed experiments using a variety of peroxidation initiators and microsomes obtained from normal and vitamin E-deficient rats. We found that lung microsomes obtained from normal rats are peroxidized much less than liver microsomes obtained from the same animals. Only initiation syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

1989
1989
2000
2000

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 0 publications
1
4
0
1
Order By: Relevance
“…5). Like the studies of Franco and Jenkins (1986), the data from these experiments support the hypothesis that reduced glutathione directly inhibits lipid peroxidation.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…5). Like the studies of Franco and Jenkins (1986), the data from these experiments support the hypothesis that reduced glutathione directly inhibits lipid peroxidation.…”
Section: Discussionsupporting
confidence: 72%
“…There is contradictory evidence as to whether GSH directly protects microsomal lipids from oxidation. Franco and Jenkins (1986) report direct inhibition of lipid peroxidation. Leedle and Aust (1990) maintain that GSH does not have an inhibitory effect independent of vitamin E. There is also disagreement as to whether GSH directly reduces oxidized vitamin E (Niki et al, 1982) or interacts with a membranebound vitamin E reductase (Leedle and Aust, 1990).…”
Section: Discussionmentioning
confidence: 98%
“…Incorporation of a-tocopherol in the subcellular membranes may prevent the oxidation of thiol-containing enzymes (glutathione reductase, glutathione peroxidase) which are involved in the destruction hypdroperoxides that form in the system. Franco and Jenkinson (1986) demonstrated that glutathione was effective in decreasing the rate of lipid peroxidation in microsomes from rats fed normal diets, while microsomes from rats fed vitamin E-deficient diets were more rapidly oxidised under the same peroxidative conditions. These results suggest that a-tocopherol and thiol-containing enzymes function cooperatively, in preventing free radical attack on the membranes.…”
Section: Concentration Of A-tocopherol (Hg/g Membrane Wet Basis) In mentioning
confidence: 98%
“…Additionally, it was shown that in adult respiratory distress syndrome, a vitamin E deficiency occurs that is leading to increased lipoperoxidation [ 36]. Moreover, experimental studies exhibited that vitamin E deficiency exacerbates lung damage in animals exposed to hyperoxia [ 24, 25].…”
Section: Discussionmentioning
confidence: 99%
“…If vitamin E is deficient and if free radicals are generated at a rate exceeding the antioxidant capacities of the organism, free‐radical reactions will be highly toxic for lung tissue. It has been also reported that a vitamin E deficiency exacerbates lung damage after inhalation of oxidants [ 24–26], but so far there have been no studies on whether administration of vitamin E during in vivo NO 2 exposure of type II pneumocytes will attenuate or mitigate the NO 2 ‐induced alterations of the phospholipid metabolism.…”
Section: Introductionmentioning
confidence: 99%